2016
DOI: 10.1055/s-0042-102619
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Effect of Calcium Channel Blockers on the Optic Nerve Compartment Syndrome

Abstract: To some extent, the optic nerve compartment syndrome is related to the combination of primary open angle glaucoma and Flammer syndrome. On the basis of our results, we hypothesise that treatment of Flammer syndrome may also improve the optic nerve compartment syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
16
0
2
Order By: Relevance
“…The involvement of FS has already been described for the following diseases: retinitis pigmentosa [11, 4143], Leber’s hereditary optic neuropathy [44], optic nerve compartment syndrome [45, 46], retinal vein occlusions [11, 47, 48], cilioretinal artery occlusion [49], choroidal infarction [50], Susac syndrome [11], anterior ischemic optic neuropathy [11], central serous chorioretinopathy, [11], multiple sclerosis [34], and perioperative visual loss during general anesthesia [51, 52]. The relationship between FS and breast cancer has already been suggested [53] and some first results are presented in this issue of this journal.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of FS has already been described for the following diseases: retinitis pigmentosa [11, 4143], Leber’s hereditary optic neuropathy [44], optic nerve compartment syndrome [45, 46], retinal vein occlusions [11, 47, 48], cilioretinal artery occlusion [49], choroidal infarction [50], Susac syndrome [11], anterior ischemic optic neuropathy [11], central serous chorioretinopathy, [11], multiple sclerosis [34], and perioperative visual loss during general anesthesia [51, 52]. The relationship between FS and breast cancer has already been suggested [53] and some first results are presented in this issue of this journal.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to differences of fluid composition, reduced CSF exchange and an extension of the optic nerve sheath diameter due to increased pressure [222, 264274]. We observed that ONCS was often related to PVD [2] and that treatment of FS with a low dose of CCBs also reduced ONCS [275]. …”
Section: Choroidal Infarctionmentioning
confidence: 99%
“…On the occasion of the last consultation (2016) for this patient, we conducted two additional examinations not available in our clinic previously, namely: measurement of the RVP [5] and eye socket echography, searching for ONCS [6]. While the RVP is equal to or slightly higher than the IOP in healthy subjects, it is often increased in patients with ophthalmic and systemic diseases [5], such as NTG.…”
Section: Case Presentationmentioning
confidence: 99%
“…This leads to the extension of the optic nerve sheath diameter and an altered chemical composition of the cerebrospinal fluid. ONCS has often been demonstrated in patients with NTG [4], particularly in the presence of FS [6]. However, the pathogenesis of ONCS has not yet become totally clear.…”
Section: Case Presentationmentioning
confidence: 99%